POLITICS THROUGH FASHION: JOKOWI, SEMIOTICS, AND THE AGE OF SOCIAL MEDIA - Mawar Sharon Terang; I Ketut Putra Erawan; Anak Agung Sagung Mirah Mahaswari Jayant (JWP (Jurnal Wacana Politik), 2023)
This study explores the complexity of Jokowi’s political fashion as a visual marker of status, identity, and political power, along with the digital technology advancement. The purpose of this article is to analysed details about Jokowi’s political power through fashion, which is related to five specific moments during the 2019 political campaign until his current leadership. The authors classified two typologies of clothing, including white and black shades of casual clothes and Indonesia’s traditional clothes. Roland Barthes’s semiotics theory and methods helps us to interpret series of symbols on Jokowi’s clothing. This is a qualitative research with document analysis procedure, including electronic material contain text and images (Jokowi’s Instagram archives) related to the main issue. Research shown that clothing wasn’t just an everyday business for Jokowi, but it is also tools that brands his personal identity. Public attention is often stolen when he incorporates local elements in his fashion style. The value of diversity (Kebhinnekaan) in Jokowi’s traditional clothing appearance couldn’t be separated with his identity as a president, as political figure, as Jokowi.